Controlled synthesis of Sn-based oxides via a hydrothermal method and their visible light photocatalytic performances. Issue 43 (22nd May 2017) - Wang, Jinghui; Li, Hui; Meng, Sugang; Ye, Xiangju; Fu, Xianliang; Chen, Shifu
Abstract : Controlled synthesize of Sn-oxides was achieved via a facile hydrothermal method with SnCl2 as precursor. A visible light photocatalytic activity of SnO2 can be induced by doping with Sn 2+ or coupling with SnO. Abstract : Controlled synthesis of Sn-based oxides with a different valence state is still a challenge. Here, we developed a facile hydrothermal method for selective preparation of SnO2, Sn 2+ doped SnO2 (Sn 2+ –SnO2 ), and SnO/SnO2 composites, and SnO with SnCl2 as a precursor. The valence state of Sn was regulated successively from Sn 4+ to Sn 2+ through controlling the hydrothermal solution from an O2 -rich to an O2 -deficient atmosphere, which was achieved by adding H2 O2 or urea into the solution. The structure, absorption, morphology, and the visible light photocatalytic performance of the products were investigated systematically. SnO2, Sn 2+ –SnO2, SnO/SnO2, and SnO could be prepared in a H2 O2 -contained, H2 O, urea-contained, and N2 purged urea-contained solution, respectively. For Sn 2+ –SnO2, the doping amount of Sn 2+ could be further tuned by varying the hydrothermal temperature, while for SnO/SnO2, the coupling amount of SnO could be controlled by the dosage of urea. Visible-light-induced photocatalytic degradation of methyl orange was achieved successfully on Sn 2+ –SnO2 and SnO/SnO2 . However, further work is still required to improve the stability of the samples due to vulnerability of Sn 2+ .